2016
DOI: 10.1371/journal.pmed.1002039
|View full text |Cite
|
Sign up to set email alerts
|

Plant-Based Dietary Patterns and Incidence of Type 2 Diabetes in US Men and Women: Results from Three Prospective Cohort Studies

Abstract: BackgroundPlant-based diets have been recommended to reduce the risk of type 2 diabetes (T2D). However, not all plant foods are necessarily beneficial. We examined the association of an overall plant-based diet and hypothesized healthful and unhealthful versions of a plant-based diet with T2D incidence in three prospective cohort studies in the US.Methods and FindingsWe included 69,949 women from the Nurses’ Health Study (1984–2012), 90,239 women from the Nurses’ Health Study 2 (1991–2011), and 40,539 men from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

32
587
6
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 690 publications
(720 citation statements)
references
References 53 publications
32
587
6
5
Order By: Relevance
“…In a previous analysis,(14) we found similar associations of these three indices with type 2 diabetes. Our current analysis extends the potentially protective association with hPDI to CHD.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…In a previous analysis,(14) we found similar associations of these three indices with type 2 diabetes. Our current analysis extends the potentially protective association with hPDI to CHD.…”
Section: Discussionsupporting
confidence: 78%
“…(14) We created 18 food groups based on nutrient and culinary similarities within the larger categories of healthy plant foods, less healthy plant foods, and animal foods (Table 1). Given that alcoholic beverages have different directions of association for various health outcomes, and margarine’s fatty acid composition has changed over time from high trans to high unsaturated fats, we did not include these foods in the indices, but adjusted for them in the analysis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In short-term trials, supplemental magnesium intake exerts small beneficial effects on parameters of glucose and insulin metabolism (4). Prospective observational literature (59) supports an inverse association between magnesium intake and incident type 2 diabetes as well as precursor physiological states (i.e., insulin resistance and prediabetes), the latter suggesting potentially amplified roles of magnesium in the context of dietary factors related to these precursor states, such as carbohydrate load or unhealthful diets known to elevate type 2 diabetes risk (1012). For example, inverse associations between magnesium and type 2 diabetes may be more pronounced in those with higher glycemic index (GI) or glycemic load (GL) diets, because higher GI and GL induce higher insulin demand, and magnesium is required for insulin signaling and action (13,14).…”
Section: Introductionmentioning
confidence: 99%
“…A prospective cohort study in USA showed an inverse association between a healthy plant‐based diet and type 2 diabetes. However, there was also an association between unhealthy plant foods and risk of type 2 diabetes . In Middle‐Eastern countries, there is a dietary pattern of plant‐based foods that partially consists of refined grains including white rice and bread .…”
Section: Introductionmentioning
confidence: 99%